Letter: is the radiation therapy causing an IBD flare, or the IBD predisposing to radiation toxicity?. Issue 7 (11th March 2021) - Lim, Gerald; Kassam, Zahra; Seow, Cynthia H.
Abstract : LINKED CONTENT This article is linked to Broussard et al and Laharie & Riviere papers. To view these articles, visit https://doi.org/10.1111/apt.16176 and https://doi.org/10.1111/apt.16300